Vitamin D Deficiency among Well Nourished and Malnourished Children of School Going age at District Tharparkar - Aneel Kapoor, Fasiha Fatima, Naveed Ahsan, Ghulam Serwar Shaikh, Dildar Ali Solangi, Bhawni Shanker (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The most frequent type of nutrient shortage is Vitamin D deficiency, which affects about of half of the world’s population. Vitamin D deficiency responsible for numerous acute and chronic conditions not only in malnourished children but also in well-nourished children. Our objective was to determine vitamin D levels among malnourished and well-nourished school going children at district Tharparkar Pakistan. Design: Cross-sectional study Setting: This study was conducted in Mithi, District Tharparkar among school age-children (between 10-18 years). Vitamin D was estimated by Cobas e411 analyzer Roche (made in Japan). Results were descripted as mean ± SD. Students t test was used to find out the significant of results. A 0.05 or lower p -value was judged as meaningful. Results: 300 children were divided in malnourished and well-nourished groups. Vitamin D deficiency affected 74% of school age children. Boys accounted for 30% of the group, while girls made up 44%. We noticed that 4 girls had severe vitamin D deficiency. Conclusion: Vitamin D deficiency is more prevalent in school going children. Even well-nourished girls are more vitamin D deficit than boys. Children are seen as important members of society and are regarded as the country’s future architects. As a result, investing in children’s health is the most important factor in improving Pakistan’s economic, political, and social conditions, because malnutrition has a significant impact on mental and physical inadequacy. Keywords: Vitamin D, Malnutirion, school going children